The Methodology of Reforming Islamic Law Fatwa Bahthul Masail Nahdhatu Ulama in Family Planning (KB) in Indonesia by the Maqasid Shari'ah Approach - Hakim, Abdul; Ahmad, Ridzwan; Jaafar, Syed Mohd Jeffri Syed (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This research aims to find out the renewal of NU (nahdatul ulama)'s fatwa of Bahsul Masail about the law of family planning (KB, keluarga Berencana, or family planning) in Indonesia, where it started from a law of haram, makruh, and halal. It specifies conditions through the maqasid shari'ah approach as a renewal of Islamic law. This study utilizes qualitative and descriptive analytical methods using a maqasid approach. In addition, the data that is obtained is analyzed descriptively by using deductive ideation methods. The results of this study are: 1) The reason for changing the legal fatwa on family planning( KB) from haram, makruh, and halal with condition is because of a new 'illat, namely the demands of the times. 2) Bahthul Masail NU agrees to the new fatwa under certain conditions. 3) The renewal of the new Family Planning Fatwa through the maqasid sharia approach can be carried out not only to avoid economic downturns but also to save the nation's children from caretakers, disease, low morality, faith, and crime, as well as other social ailments. Regarding the permissibility of the Bahtsul Masail Family Planning Program, NU has already paid attention to its goals (maqasid) and the conditions of society because family planning is essentially only a means or tool (wasail) to achieve goals (maqasid). Means for good and maslahah are considered permissible and sunnah, while means for evil and harm are considered makruh and unlawful.